2015
DOI: 10.1186/s40064-015-1581-7
|View full text |Cite
|
Sign up to set email alerts
|

Melting dynamics of short dsDNA chains in saline solutions

Abstract: DNA melting has attracted much attention due to its importance in understanding the life-reproduction and metabolism and in the applications of modern DNA-based technologies. While numerous works have been contributed to the determination of melting profiles in diverse environments, the understanding of DNA melting dynamics is still limited. By employing three-site-per-nucleotide (3SPN) double-stranded DNA (dsDNA) model, we here demonstrate the melting dynamics of an isolated short dsDNA under different condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 53 publications
1
0
0
Order By: Relevance
“…We hence examine the melting of the individual base pair and found that they melt sequentially, starting with one of the end base pairs. In agreement with previous simulations, 47,48 we observe that the speed of base-pair dissociation generally becomes larger and larger during the melting process (see Fig. 6).…”
Section: B Dna Melting Kineticssupporting
confidence: 93%
“…We hence examine the melting of the individual base pair and found that they melt sequentially, starting with one of the end base pairs. In agreement with previous simulations, 47,48 we observe that the speed of base-pair dissociation generally becomes larger and larger during the melting process (see Fig. 6).…”
Section: B Dna Melting Kineticssupporting
confidence: 93%